ملامح نظرية ابن خلدون التربوية (Comprehensive Journal of Science, 2025)
This study aims to identify the features of Ibn Khaldun's educational theory. He is considered one of the first Muslim intellectuals to contribute to the phenomenon of education. In his book "Al-Ibar," he classified sciences into rational and transmitted, presenting his educational views, which have been confirmed by modern studies. These views include the need to prioritize the teacher and teaching methods, diversify teaching methods, and take into account individual differences among learners.The researcher recommends studying Ibn Khaldun's, Theory, educational